Diagnostic Performance of Mac 2–Binding Protein Glycosylation Isomer in Chronic Hepatitis B - Wita Prominensa; B. Rina A. Sidharta; Lusi Oka Wardhani; JB. Suparyatmo; MI. Diah Pramudianti (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Chronic Hepatitis B (CHB) is a concern for Chronic Liver Disease (CLD) and causes a 74% mortality rate in Asia Pacific. World Health Organization (WHO) showed Indonesia is the highest second country of Hepatitis B (HB) in the South East Asian Region, Central Java is the highest in Java and Dr. Moewardi Hospital (RSDM) Surakarta in 2019 increased to 15%. Liver biopsy is fibrosis gold standard staging. It has limitations and requires invasive procedure pain in 40% of patients. This study aimed to determine M2BPGi diagnostic test against to transient elastography (TE) Fibroscan® (sensitivity 85.7%, specificity 81.6%) as a predictor of significant liver fibrosis of CHB in RSDM. Fibroscan® examination was performed on patients diagnosed with CHB by a clinician performed at the endoscopy department of RSDM, whereas laboratory tests were carried out from December 2020 to January 2021. Plasma M2BPG-I cut-off value was determined using Receiving Operating Characteristic (ROC) curve, M2BPGi levels were measured sandwich ELISA using spectrophotometry at a wavelength of 450 ± 2 nm. A total of 70 subjects was divided into 35 subjects with significant and 35 subjects with non-significant fibrosis. The results of the statistical calculation showed that plasma M2BPGi levels had a cut-off of 12.939 ng/mL (mean value of 17.841 ng/mL with significant fibrosis at 16.74 ng/mL and non-significant fibrosis at 10.14 ng/mL) had a moderate performance as a marker of liver fibrosis in CHB (71.4% sensitivity; 68.6% specificity; 69.4% PPV; 70.6% NPV and PLR 2.273), NR 0.417 with AUC of 0.727, CI 96% (0.681-0.0906). M2BPGi plasma levels at a cut-off of 12.939 ng/mL had a moderate performance as a predictor of significant liver fibrosis in chronic hepatitis B patients.